Fluorescence studies of a silane gel to be applied as a carrier in optical sensors. (2005) - Miller, Ewa; Wysocki, Stanisław; Jóźwik, Donata
Abstract : Results of fluorescence studies on the degree of pyrene and aminopyrene elution from a silane gel by water and ethanol are discussed in the paper. The studies were carried out for gels obtained on glass plates that differed in composition. Silane monomers: TEOS—tetraethylorthosilane, APTES—3-aminopropyltriethoxysilane, GPTMS—3-glycidoxypropylmethoxysilane, PDMS—polydimethylsilane, TMAOH—tetraethylammonium hydroxide, water and ethanol were used. A fluorophore was trapped in the gel either physically or using covalent bonds with the amino group of a carrier and glutaraldehyde. Emission spectra of the probe steady-state fluorescence in the gel were recorded on subsequent days of storage of plates with the gel in fresh solvent. The kinetics of aminopyrene decay in the sol and silane gel was also recorded. On the basis of results obtained, the degree of elution of fluorophore from the gel was determined in view of the application of the silane gel as a carrier in the optical sensor and the nature of the probe environment.